METHODS OF IDENTIFYING NEUROLOGICAL DELIRIUM (MIND) STUDY - Mulkey, Malissa Ann (East Carolina University)
Delirium is a major concern for critically ill older patients because it is associated with significant risk to quality of life and mortality. The United States spends approximately $164 billion in Medicare funding annually to combat the consequences of delirium. This figure is only expected to increase as the number of individuals aged 65 years or older increases. By 2030, one in four individuals in the United States will be 65 years old or older. Of further concern is that more adults are surviving critical illness and are therefore living with more comorbidities. Currently, as many as 80% of adults in intensive care units develop delirium. Unfortunately, healthcare providers fail to recognize 80% of these cases. Delirium is an acute fluctuating disorder impacting attention and global cognitive function with an underlying organic cause. As the brain attempts to adapt to overwhelming stress, reductions in cortical activity result in neurotransmitter imbalances. These imbalances are reflected electrographically on electroencephalogram (EEG). Once the ability to compensate has been exhausted, behavioral symptoms associated with delirium begin to appear. Standardized assessments for delirium need to be capable of early, accurate, and objective identification. EEG is the gold standard for delirium detection but is not always feasible due to cost, technical setup, and need for skilled interpretation. Currently available instruments, while effective in the clinical research setting, have not translated well into practice. As a result, they fall short of accurate detection for a variety of reasons, including intermittent and retrospective data collection and requiring examiner interpretation. The lack of objective physiological monitoring capability for delirium detection prevents nurses and other healthcare providers from proactively managing this debilitating clinical problem. Because nurses provide frontline care to this patient population, the lack of adequate methods for detection presents a gap in nursing science. Recently developed technology, signal processed limited lead EEG, may provide an alternative to traditional monitoring methods for delirium. Limited lead EEG can provide the EEG waveform information needed to determine delirium status, is much cheaper than traditional EEG and can be applied by nurses, thereby overcoming limitations seen with traditional EEG such as cost and technical set-up. Critical care nurses currently use this type of EEG for sedation titration and monitoring. Because these monitors can analyze the most reliable biomarker, EEG, they may provide much needed objective, accurate, early identification of delirium. The design for this study was prospective exploratory and cross-sectional. After appropriate Institutional Review Board permissions, a convenience sample of patients were recruited from the cardiac, medical and surgical intensive care units in a large southeastern academic medical center. Study data were collected by the author and prepared for analysis. Analytical methods included descriptive statistics, statistical methods to compare groups, and statistical methods to explore relationships among variables. Study results were then described and discussed.
Keywords: Delirium; Risk factors